When prices spike: Identifying excessive volatility in fertilizer markets - Yao, Feng; Hernandez, Manuel A. (Elsevier, 2026)
Sharp and volatile fertilizer price movements can hinder adoption and reduce agricultural productivity, especially among vulnerable smallholders. Using a nonparametric location-scale approach to model price returns, we quantify the conditional value-at-risk (CVaR)—the high return threshold exceeded with low probability—to identify excessive price spikes in potash, urea, and di-ammonium phosphate (DAP) markets. We use the bias-corrected estimator from Martins-Filho et al., (2018) and propose a simpler estimator based on Hill (1975). Backtesting results indicate superior performance of the Hill-based estimator, supporting its value as a convenient method for detecting unusual fertilizer price surges amid recurring global volatility.